Utilization of waste from trimming process for the development of pangasius fish nugget - Laudya Jenita; Fransisca; Agus Purnomo Wibisono (Hasanuddin University Food Science and Technology Study Program, 2022)
Currently, the processing of pangasius fish is limited in most industries in Indonesia. This fish can be processed into nuggets, but the texture is a common issue determined by the composition of the meat and fat. Therefore, optimal composition is needed to produce the desired texture. The fat used was derived from the trimmings, waste of the Pangasius fillet factory. This study, then, aims to determine the effect of substitution of fillet with trimmings on chemical and sensory characteristics of fish nugget. Furthermore, it obtains the best formulation using 6 ratios of fillet and trimmings at 100:0, 60:40, 50:50, 40:60, 30:70, and 20:80. Proximate analysis of moisture, ash, carbohydrate, protein, and fat content was conducted, while acceptance testing was used in sensory analysis. The results showed that the substitution of trimmings only resulted in significant difference in fat content. This is due to the direct proportionality between the percentage of trimmings, and the fat content of nuggets. Meanwhile, the sensory analysis only resulted in significant differences in crispness, hardness and overall. In conclusion, nugget with 20:80 treatment was the best formulation because it has the highest preference value and can utilize waste optimally.